2004
DOI: 10.1016/j.cbpc.2003.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Swim exercise training and adaptations in the antioxidant defense system of myocardium of old rats: relationship to swim intensity and duration

Abstract: We examined a suitable swim program of different intensities and durations that could evoke changes in the myocardial antioxidant capacity in 22-month-old rats. Male rats (Rattus norvegicus) were assigned to either a sedentary control (SE-C) group or one of six trainee groups. Animals were swim-exercised for 4 weeks with either 20 min or 40 miny day, and three intensities, low, moderate and high. Low-intensity at 20 minyday elicited maximum swim velocity (S ) v and endurance capacity (P-0.05). While serum tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 39 publications
3
30
0
3
Order By: Relevance
“…In the current study we chose swimming as a model of physical effort because it is a method that causes less mechanical stress and injury and produces a redistribution of the blood flow to the tissues without significant variations in the heart rate and cardiac output, minimizing the intensity of injuries caused by the generation of ROS (9,23,31,35). Our results, consistent with recent studies, showed that moderate swimming training decreased glycemia in diabetic rats (3,15).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the current study we chose swimming as a model of physical effort because it is a method that causes less mechanical stress and injury and produces a redistribution of the blood flow to the tissues without significant variations in the heart rate and cardiac output, minimizing the intensity of injuries caused by the generation of ROS (9,23,31,35). Our results, consistent with recent studies, showed that moderate swimming training decreased glycemia in diabetic rats (3,15).…”
Section: Discussionsupporting
confidence: 87%
“…The implication of oxidative stress in insulin resistance and in the pathogenesis of DM is explained not only through the generation of reactive oxygen and nitrogen species (RONS) but also through the alteration of endogenous antioxidant enzymes. Hyperglycemia generates RONS through multiple pathways such as: the activation of nuclear factor (NF)-κB which increases the expression of inducible nitric oxide synthase (iNOS) and the increased generation of nitric oxide (9); increased mitochondrial production of the superoxide anion radicals (37); glucose autoxidation (31); non-enzymatic glycation of proteins (25,26); the activation of protein kinase C (18); etc. Nitric oxide reacts with the superoxide and forms peroxynitrite, which is a strong oxidant that increases lipid peroxidation, protein nitration and LDL oxidation.…”
mentioning
confidence: 99%
“…The GPX is an antioxidant enzyme that plays a role in removing free radicals and reducing their damage. In agreement with the findings of present study, others showed that endurance exercise has no significant effect on MDA of cardiac tissue in male rats (23,(32)(33)(34)(35)(36). In addition, another study reported that chronic administration of 10 mg/kg of nandrolone for 14 weeks did not have significant effect on GPX level in rats (37).…”
Section: Discussionsupporting
confidence: 82%
“…Physical exercise has possessed a key role in tissue homeostasis, associated with increased antioxidant defenses as well as decreased systemic inflammation [27,28,29] . In addition, although exercise training can be considered as a stressor that is able to increase plasma catecholamine concentrations; [30] however, catecholamine concentrations are influenced by many factors as gender and age in response to exercise [31] .…”
Section: Introductionmentioning
confidence: 99%